Beyond the glutamate N-methyl D-aspartate receptor in major depressive disorder: The mToR signaling pathway [Majör depresif bozuklukta glutamat N-metil-D-aspartat reseptörlerinin ötesi: MTOR sinyal yolaǧı] - (:unkn) unknown (Cukurova Univ Tip Fakultesi Psikiyatri Anabilim Dali, 2011)
Conventional antidepressants acting through serotonin and/or noradrenaline fail to help about half of depressed patients and even when effective, they have a delayed onset of therapeutic response. Accumulating evidence suggests that the glutamatergic system plays an important role in the neuropathology and treatment of major depressive disorder (MDD). Recently it has been shown that ketamine has a rapid and long lasting antidepressant activity after a single dose. Ketamine has been used as a human and animal anesthetic. It acts on the human brain by blocking the N-methyl-D-aspartate receptors (NMDARs), which receive nerve signals carried by glutamate; however, in a very recent Yale University study, published in the August issue of Science, the exact mechanism of ketamine's action has been identified. In studies with rats, basic researchers demonstrated that ketamine rapidly activates the so called "mammalian target of rapamycin" (mTOR) pathway, one of many such pathways that perform signal transduction in neurons. This new approach may be a revolutionary break-through in the treatment of depression and it might lead to novel therapeutic targets for antidepressant drug development.
Keywords: Glutamate; Ketamine; Mammalian target of rapamycin; mToR; N-methyl-D-aspartate receptor